2016
DOI: 10.1088/1674-1056/25/12/126701
|View full text |Cite
|
Sign up to set email alerts
|

Landau damping in a dipolar Bose–Fermi mixture in the Bose–Einstein condensation (BEC) limit

Abstract: By using a mean-field approximation which describes the coupled oscillations of condensate and noncondensate atoms in the collisionless regime, Landau damping in a dilute dipolar Bose-Fermi mixture in the BEC limit where Fermi superfluid is treated as tightly bounded molecules, is investigated. In the case of a uniform quasi-two-dimensional (2D) case, the results for the Landau damping due to the Bose-Fermi interaction are obtained at low and high temperatures. It is shown that at low temperatures, the Landau … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The phenomenon of BEC was first proposed by Einstein in 1924, who showed that a noninteracting bosonic gas can undergo a phase transition below a critical temperature to macroscopically populate the ground state. In recent years, the BEC-like phase transition has been observed in several physical systems, [15][16][17][18][19][20] including atomic gas, exciton polaritions, solid-state quasiparticles, and so on. It is well known that essentially the laser beam or electromagnetic field can be considered as a boson system consisting of photons.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of BEC was first proposed by Einstein in 1924, who showed that a noninteracting bosonic gas can undergo a phase transition below a critical temperature to macroscopically populate the ground state. In recent years, the BEC-like phase transition has been observed in several physical systems, [15][16][17][18][19][20] including atomic gas, exciton polaritions, solid-state quasiparticles, and so on. It is well known that essentially the laser beam or electromagnetic field can be considered as a boson system consisting of photons.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Landau damping has been studied in plasmas with different distribution functions. [30][31][32][33][34] Liu et al [33] derived the generalized dispersion equation for longitudinal oscillation in an unmagnetized, collisionless, isotropic and relativistic plasma in the context of nonextensive q-distribution.…”
Section: Introductionmentioning
confidence: 99%